Fertility Preservation in Endometriosis Patients: Anti-Müllerian Hormone Is a Reliable Marker of the Ovarian Follicle Density - Garavaglia, Elisabetta; Sala, Cinzia; Taccagni, Gianluca; Traglia, Michela; Barbieri, Caterina; Ferrari, Stefano; Candiani, Massimo; Panina-Bordignon, Paola; Toniolo, Daniela (Frontiers in Surgery, 2017)
Objective: To analyze the ovarian reserve via measurement of follicular density and AMH in endometriosis patients participating to a clinical program of cortical ovarian cryopreservation. Design: Retrospective analysis of serum AMH levels and prospective investigation of ovarian follicle number. Setting: University Hospital. Patient(s): Two hundred and two women with endometriosis and 400 controls. Intervention(s): Blood samples and ovarian biopsies. Main Outcome Measure(s): Correlation of serum AMH levels and the number of non-growing follicles in the biopsied cortical tissues in endometriosis and control subjects, including age, type of AMH kit, and the laboratory performing the analysis as covariates. Result(s): AMH levels were shown to decrease with age in untreated endometriosis patients (P <1.0x10-5) but they were significantly lower in endometriosis compared to controls only in patients over 36 years old (P = 2.7x10-4). The AMH decrease was faster in endometriosis compared to controls (beta = 0.27, P = 4.0x10-4). Primordial follicle number decreased with the reduction of AMH levels in both cases and controls (beta = 0.3; P = 0.04). Conclusion(s): AMH is a reliable marker of ovarian reserve in endometriosis patients and it can predict follicular density in women undergoing ovarian tissue cryopreservation.